ANALISIS HUKUM PUTUSAN HAKIM DALAM PERKARA PERSELISIHAN HAK DI PENGADILAN HUBUNGAN INDUSTRIAL PEKANBARU(STUDI KASUS TERHADAP PUTUSAN NOMOR 24/G/2012/PHI.PBR) - Tria Hasanudin; Rika Lesatari; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Rights dispute is a dispute arising out of one of the parties to the agreement does notmeet thelabor content of the agreement or violate the provisions of the law. The impact of these rightsdisputes, very complex, and tends to give rise to disputes. Therefore, mechanisms and procedures rights disputes has been arranged so that workers / laborers are in dispute Rights obtain adequate protection and obtaining their rights in accordance with the provisions. Since the release of Act No. 2 of 2004 concerning Industrial Relations Dispute Settlement, handling disputes rights disputes are handled by the Industrial Relations Court to the Court of Industrial Relations. The purpose of this study was to analyze the basic consideration in the Industrial Relations Court case decision No. 24 / G / 2012 / PHI.PBR as well as to determine whether the decision of the Industrial Relations Court No. 24 / G / 2012 / PHI.PBR in the case of rights disputes have fulfilled the principle of legal certainty in the fulfillment of the rights of workers / laborers. This type of research used by the author in the study is a normative legal research. Researchers in this case it discusses the general principles of law. The result obtained there are two main issues, The first a basic consideration in examining judge and decide the case number 24/G/2012/PHI.PBR not pay attention to sociological aspects of workers laborers who have worked so as it should they get their rights in accordance with article 168 paragraph (3) of law No. 13 of 2003. The second, the trial judge’s decision industrial relations does not satisfy the principle of legal certainty because it does not give rights of workers laborers in accordance with law number 13 of 2003. Suggestion of writers against, problems studied, The first in considering a case the judge must consider the normative sociological philosophical aspects. The second verdict must satisfy in accordance with article168 paragraph (3) of law No. 13 of 2003.Keywords: Decision Judge -Dispute of Rights- Certainty of law